Analisis Penambahan Serat Sabut Kelapa pada Campuran Beton - Sudirman Latjemma (PT FORMOSA CENDEKIA GLOBAL, 2022)
In the current technological era, concrete is one of the most widely used building materials in Indonesia, therefore good quality concrete will greatly support structural safety. In general, the people of Tolitoli have a lot of income from plantations, one of which is coconut plantations located in Dampal Selatan District, Tolitoli Regency. There are quite a lot of coconut plantations, and this causes the presence of coco fiber waste. In this study, the materials used for normal concrete mixtures consist of water cement, fine aggregate and coarse aggregate. The water used to mix the concrete is taken from the PDAM channel. To add coconut fiber to the concrete mix to determine the effect of adding coconut fiber to the compressive strength of concrete. The test objects to be made using a cube with a diameter of 150 mm, a width of 150 mm and a height of 150 mm, a total of 16 specimens with the design requirements, the compressive strength is based on the results of the compressive strength of the cube which has a size of 150x150x150 mm. to determine the compressive strength of cube-shaped concrete made and treated in the laboratory. The compressive strength of concrete is the load per unit area that causes the concrete to crumble. That is by performing a compressive test of concrete with a concrete compressive test tool that is available at the laboratory of the public works and spatial planning department of the Tolitoli district. The results obtained from the data analysis showed that the compressive strength of normal concrete at the age of 28 days was 22.63 MPa, for concrete with the addition of 0.5% coconut coir fiber at the age of 28 days it produced a compressive strength of 17.43 MPa, and decreased by 22.97% of the compressive strength of normal concrete, and concrete with the addition of 1.5% coconut coir fiber at the age of 28 days produced a compressive strength of 13.92 MPa and decreased 38.49% of the normal concrete strength, and for concrete that had added coconut coir fiber of 2.5% produces a compressive strength of 9.91 Mpa at the age of 28 days, a decrease of 56.21% from the normal compressive strength of concrete. 5% does not reach the planned concrete strength, which means that it is not yet suitable for use for 20 MPa concrete.